STATUS PARITAS DENGAN TEKNIK MENYUSUI PADA IBU POST PARTUM - Pasiak, Sri Meyke; Pinontoan, Odi; Rompas, Sefty (JURNAL KEPERAWATAN, 2019)
Abstract:Breastfeeding is the ideal way for mom to express affection on her daughter and thebest way for mom to paint food full of nutrients, but the reality is still a lot of mothers whocannot breastfeed by breastfeeding Technique. Methods this study used a cross-sectionalresearch design cros with entire population mother post!, in Clinics And health centers inManado Tuminting Wori Minut, using primary data interviews and observations as well assecondary data obtained from the clinic. Samplingis done in a non probability sampling withpruposive samplingtechniques. The number of samples as many as 47 respondents. The datapresented in the form of a Frequency Table, the analysis of the data used is the analysis ofunivariate and bivariat analysis method using chi-square. Research results based on thecharacteristics of the mother post!, respondents have age 19-25 years, educated in highschool, and worked as the IRT Primipara and Multipara parity with, the majority ofrespondents who do good on nursing Techniques parity multipara (59.6%), sedangankanrespondents who do less good feeding Techniques on primipara parity. Test results of chisquare.Get results in a value of p = 0.01 smaller than Î± = 0.05. In conclusion, the results ofthis study showed no connection between status which meant parity with the technique ofbreastfeeding on maternal post.Keywords:Status Of Parity, Breastfeeding TechniquesAbstrak: Menyusui merupakan cara yang ideal bagi ibu untuk mengekspresikan kasih sayangpada anaknya dan cara terbaik bagi ibu untuk memberikan makanan yang penuh gizi, namunkenyataan masih banyak ibu yang tidak dapat menyusui dengan teknik menyusui yang benar.Metode penelitian ini menggunakan desain penelitian cros sectional dengan populasi seluruhibu post partum di Puskesmas Tuminting Manado Dan Puskesmas Wori Minut, denganmenggunakan data primer wawancara dan observasi serta data sekunder yang didapat daripihak Puskesmas. Pengambilan sampel dilakukan secara non probability sampling denganteknik pruposive sampling. Jumlah sampel sebanyak 47 responden. Data disajikan dalambentuk Frequency Table, Analisis data yang digunakan adalah analisis univariat dan bivariatdengan menggunakan metode analisis chi-square. Hasil penelitian berdasarkan karakteristikibu post partum, responden memilki usia 19-25 tahun, Berpendidikan SMA, dan bekerjasebagai IRT dengan paritas Multipara dan Primipara, mayoritas responden yang melakukanTeknik menyusui yang baik pada paritas multipara (59,6%), sedangkan responden yangmelakukan teknik menyusui yang kurang baik pada paritas primipara. Dari hasil ujichisquaredidapatkanhasil nilai p = 0,01 lebih kecil dari Î± = 0,05. Kesimpulan, hasil penelitianini menunjukan ada hubungan yang bermakna antara status paritas dengan teknik menyusuipada ibu post partum.Kata Kunci:Status Paritas, Teknik Menyusui